2020
DOI: 10.21273/hortsci14490-19
|View full text |Cite
|
Sign up to set email alerts
|

Physiological Response of Cape Gooseberry Seedlings to Two Organic Additives and Their Mixture under Inoculation with Fusarium oxysporum f. sp. physali

Abstract: Vascular wilt caused by Fusarium oxysporum f. sp. physali is the most limiting disease in cape gooseberry crops. The use of natural products such as organic additives is a promising alternative for management of this disease. The present study sought to evaluate the physiological response of cape gooseberry plants infected with this pathogen and treated with the organic additives chitosan, burned rice husks, or their mixture. The test was conducted … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 52 publications
0
5
0
Order By: Relevance
“…Okorski et al [61] obtained similar responses with the application of a mixture of different BCAs (biological preparation of effective microorganisms such as lactic acid and photosynthetic bacteria and yeast), which also generated an increase in gas exchange parameters such as photosynthesis, g s, and transpiration in pea plants (Pisum sativum L.) with Fusarium oxysporum wilt symptoms. A previous study also indicated that Foph-infected cape gooseberry plants and treated with chitosan showed better gas exchange (g s ) and Ψ wf parameters compared to plants without chitosan [45].…”
Section: Discussionmentioning
confidence: 83%
See 4 more Smart Citations
“…Okorski et al [61] obtained similar responses with the application of a mixture of different BCAs (biological preparation of effective microorganisms such as lactic acid and photosynthetic bacteria and yeast), which also generated an increase in gas exchange parameters such as photosynthesis, g s, and transpiration in pea plants (Pisum sativum L.) with Fusarium oxysporum wilt symptoms. A previous study also indicated that Foph-infected cape gooseberry plants and treated with chitosan showed better gas exchange (g s ) and Ψ wf parameters compared to plants without chitosan [45].…”
Section: Discussionmentioning
confidence: 83%
“…The microorganisms selected for the mixtures were Trichoderma virens and Bacillus velezensis (formerly B. amyloliquefaciens) due to their biocontrol potential against plant pathogens [11,38]. Regarding organic additives, chitosan (Sigma Aldrich, St. Louis, MO, USA) and burnt rice husk were also selected due to their potential control of Foph observed in a previous study [45]. Eight groups of treatments were obtained for the development of the experiment: (i) cape gooseberry plants with no addition of BCAs or organic additives and inoculated with Foph (pathogenic control (Foph + )) or without it (absolute control (Foph − )); (ii) cape gooseberry plants with or without Foph inoculation and with the application of the mixture of BCAs (T. virens and B. velezensis (Mix)); (iii) cape gooseberry plants with or without Foph inoculation with the application of the mixture of BCAs and the addition of chitosan (MixChi) and (iv) cape gooseberry plants with or without Foph inoculation with application of the mixture of BCAs and the addition of burnt rice husk (MixRh).…”
Section: Treatments With or Without Foph Inoculation And The Addition Of Mixtures Of Biological Control Agents (Bcas) And Organic Additivmentioning
confidence: 99%
See 3 more Smart Citations